2009
DOI: 10.3138/cmlr.65.5.869
|View full text |Cite
|
Sign up to set email alerts
|

To Like or Not to Like! Student Perceptions of Technological Activities for Learning French as a Second Language at Five Canadian Universities

Abstract: This article examines student attitudes towards and perceptions of technological activities in the language classroom. Data collected from students (n ¼ 71) in the French language departments of five Canadian universities were used to examine which technological activities students preferred, whether and to what degree different activities were judged useful, and how frequently students perceived that they were doing these activities. Four trends emerged. First, students find computer-assisted activities usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…Although this study focused on the participants' general knowledge, experiences and perceptions of educational technology preparation and did not present specific data on pre-service English teachers, results showed that pre-service teachers did not feel comfortable with spreadsheets, databases, concept mapping, hypermedia, WebQuests, simulation tools and video editing. It should be added that the Peters et al (2009) …”
Section: Research On Learners' Perceptions Of and Attitudes Toward Wementioning
confidence: 99%
See 1 more Smart Citation
“…Although this study focused on the participants' general knowledge, experiences and perceptions of educational technology preparation and did not present specific data on pre-service English teachers, results showed that pre-service teachers did not feel comfortable with spreadsheets, databases, concept mapping, hypermedia, WebQuests, simulation tools and video editing. It should be added that the Peters et al (2009) …”
Section: Research On Learners' Perceptions Of and Attitudes Toward Wementioning
confidence: 99%
“…In the first study reviewed, Peters, Weinberg, and Sarma (2009) examined second-language learners' attitudes towards and perceptions of technological activities in a French language classroom. Seventy-one students from five Canadian universities participated in the study.…”
Section: Research On Learners' Perceptions Of and Attitudes Toward Wementioning
confidence: 99%
“…Descriptions of student perceptions have also been common in the field, often focusing on specific aspects of the language learning classroom: first language (L1) usage (Rolin‐Ianziti & Varshney, ), technology (Peters, Weinberg, & Sarma, ), the native versus nonnative class instructor (Hertel & Sunderman, ), and, in the context of incoming freshmen in a university program, preferred classroom activities (Mandell, ). Similarly, Price and Gascoigne () sought to describe more general attitudes from college students about the “importance of foreign language study” and “postsecondary foreign language requirements” (Price & Gascoigne, , p. 386).…”
Section: The Trait or Learner Orientationmentioning
confidence: 99%
“…Similarly, Price and Gascoigne () sought to describe more general attitudes from college students about the “importance of foreign language study” and “postsecondary foreign language requirements” (Price & Gascoigne, , p. 386). Usually, these studies have been interpretive in nature, depending on the analysis of essays, interviews, and other forms of data, but some, notably Peters et al (), have used surveys with Likert‐scale and rank‐order questions to ascertain student perceptions. Note that these studies, when considered together, do not create a body of coherent findings about student perceptions; they represent isolated cases of exploratory work that each contribute to a different knowledge base about disparate topics (e.g., L1 usage, technology) in language learning.…”
Section: The Trait or Learner Orientationmentioning
confidence: 99%
See 1 more Smart Citation